2016
DOI: 10.3233/thc-161200
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an anthropopathic abdominal phantom for accuracy validation of deformable image registration

Abstract: Abstract. The purpose of this study is to design and fabricate an anthropopathic abdominal phantom for accuracy evaluation of deformable image registration (DIR) algorithms in adaptive radiation therapy. The constructed deformable organs, including the liver, kidney, spleen and stomach, are made of mixture of polyvinyl chloride (PVC) and softener dioctyl terephthalate, while the rigid structures, i.e. vertebrae, are made of white cement. Relation between the PVC-softener blending ratio and organ CT number is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
3
4
0
Order By: Relevance
“…The relationship between PVC‐softener ratios and CT number was similar to those reported by Liao et al Furthermore, varying the PVC‐softener ratio linearly affects CT numbers of the TMMs (R 2 = 0.988). These findings indicate that a high degree of tissue equivalency can be optimized by varying PVC‐softener mass ratios.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The relationship between PVC‐softener ratios and CT number was similar to those reported by Liao et al Furthermore, varying the PVC‐softener ratio linearly affects CT numbers of the TMMs (R 2 = 0.988). These findings indicate that a high degree of tissue equivalency can be optimized by varying PVC‐softener mass ratios.…”
Section: Discussionsupporting
confidence: 87%
“…PVC‐based TMM samples were prepared through the following steps. (a) Weighing : raw PVC and softener materials were prepared and weighed for preparing ten samples with PVC‐softener ratios ranging from approximately 7.9 × 10 −2 to 23.1 × 10 −2 g/ml (e.g., PVC‐softener ratio of 7.9 × 10 −2 g/ml indicates 7.9 g PVC powder mixing with 100 ml of the softener) . (b) Heating and Stirring : weighed raw materials were mixed and heated to 280°C under constant stirring for 30 min .…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, we identified and reported a PVC-softener mixture that represents the physical and imaging properties of human breast tissues. A PVC-softener ratio of 12.3×10 −2 g/mL corresponds to 36.2 HU, which is similar to previous results from Liao et al (40), and also close to glandular tissues (40 HU) (36). Although the T1 and T2 relaxation times are shorter than those reported with physiologic breast tissue (54), we found the mean relaxation times of 206.81±17.50 ms for T1 and 20.22±5.74 ms for T2, as compared to published values of 1,324.42±167.63 ms and 54.36±9.35 ms, respectively (54).…”
Section: Discussionsupporting
confidence: 91%
“…The soft PVC TMM used for phantom construction was made from a mixture of PVC powder and softener (i.e., dioctyl terephthalate). A mixture of white and opaque PVC powder and softener was heated to 280 ℃ on a laboratory hot plate with constant stirring until the mixture was thoroughly polymerized and transparent (40). For breast ultrasound imaging, 3% graphite powder was added to the mixture resulting in an echo speed of 1,397.9 m/s (41), which provides sharp contrast with the insert and mimics breast tissue.…”
Section: Production Of Pvc-based Materials As Tmmmentioning
confidence: 99%